A new method to determine wound age in human skin injuries - Bitoljanu, Natasha; Risteski, Sasho; Belakaposka, Viktorija; Ivcheva, Ana; CHakar, LJupcho; Pavlovski, Goran; Stankov, Aleksandar; Krstevska Balkanov, Svetlana; Jakjovski, Zlatko (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2023)
Wound age determination is a significant part of everyday practice in forensic medicine. Determining the wound age answers a large number of questions arising from a criminal-legal event. The RT-PCR technique enables qualitative and quantitative analysis of mRNA and can register minimal changes in gene expression, which makes it more sensitive and accurate compared to the immunohistochemical method. The study included 51 wound samples of autopsy cases. In this study we conducted comparative analyses for different methods of homogenization and isolation. An analysis was carried out for the selection of a suitable reference gene that will be used for normalization of the expression levels of the investigated target gene. Two reference genes, GAPDH and 18S, were analyzed in the study. A biphasic expression of IL-6 information RNA (mRNA IL-6) was determined in relation to the other groups, including the control group. 18S has better efficiency of amplification then GAPDH. RNA was isolated from all examined tissues with the TriXact kit on the MagCore Plus II instrument. It can also be concluded that mechanical maceration of the tissue was more effective than the other methods of homogenization. 18S is a more stable reference gene for the analysis of skin samples. IL-6 can could be used as a marker in wound age determination.
Keywords: wound age; real-time PCR; autopsy cases; human dermal injuries; Il-6